Hydrogen evolution in aqueous solutions containing dissolved H2S: Evidence of direct electroactive contribution of H2S - Kittel, J.; Ropital, F.; Grosjean, F.; Tribollet, B.; Eliane, Sutter (HAL CCSD, 2012)
International audience This paper compares the cathodic reactions occurring on steel in an oxygen-free aqueous solution containing dissolved H 2 S or dissolved CO 2. It is well admitted that the rate of the cathodic reaction is enhanced in aqueous solutions containing dissolved CO 2 , in comparison with strong acid solutions at the same pH [1-6]. In a previous paper [7], the authors have shown that this phenomenon appears only in the mass transfer limitation region, where the transport of carbonic acid is added to the transport of proton. In the case of H 2 S containing solutions, this chemical mechanism is no more sufficient to explain the cathodic polarization curves. An additional electrochemical reaction is clearly observed, with strong links with H 2 S concentration.